Apamargkshar Taila Uttarbasti in the Management of Secondary Infertility Due to Tubal Blockage - A Case Study. - Ekta; Dixit, Mahesh; Meena, Narendra Kumar (International Research Journal of Ayurveda & Yoga, 2021)
Secondary Infertility occurs when a couple is fails to conceive for several years after the first delivery. Ayurveda plays important role to treat infertility for years without the help of modern medical system, as it provides ability to infertile women or couples through treatment to become fertile and also to enhance the overall health. Tubal blockage is most common causative factor for infertility which constitutes nearly one third of total infertility cases. In presence of tubal blockage there are only two options in modern medical system, re-construction of the tube, IVF. These procedures are invasive, time consuming and much costly. This article presents tubal blockage was treated with certain Ayurvedic drugs and procedures in present case. In Ayurveda probably Vata and Kapha doshas are responsible for tubal blockage, hence Shodhan Chikitsa was administered. Uttarbasti performed with Apamargkshar taila used as treatment part for tubal blockage in female infertility.